Seroprevalence of Hepatitis B virus surface antigen among African blood donors: a systematic review and meta-analysis - Angelina Edna Quintas; Angelina Edna Quintas; Nelson Cuboia; Nelson Cuboia; Lemuel Cordeiro; António Sarmento; Luís Azevedo; Luís Azevedo (Frontiers Media S.A., 2024)
BackgroundTransfusion Transmitted Infections (TTIs) are still a growing public health problem in Africa. Studies that synthesize the available evidence on the seroprevalence of Hepatitis B Surface Antigen (HBsAg) among African blood donors are scarce. Therefore, this study aimed to synthesize qualitatively and quantitatively the seroprevalence of Hepatitis B Virus Surface Antigen (HBsAg) among blood donors in Africa.MethodsWe conducted a systematic review and meta-analysis where we included all studies that reported the seroprevalence of HBsAg among blood donors in Africa. The references were searched from electronic databases: PubMed, Web of Science, Cochrane, Scopus, WHO research database-HINARI, Global Index Medicus and ClinicalTrials.gov. We further analyzed the full list of references of all included studies. The pooled seroprevalence was estimated through random effect model. The heterogeneity was assessed through Cochrane's Q test and I2, respectively. Meta-regression, subgroup and sensitivity analyses were conducted.ResultsWe obtained 124 studies that met our inclusion criteria, comprising 3,573,211 blood donors tested for HBsAg. The pooled seroprevalence of HBsAg among blood donors in Africa was 6.93% (95% CI: 5.95-7.97%; I2 = 100%; p < 0.001). We found that the heterogeneity was explained by the study performed country and, African region. The higher prevalence was observed in Western 10.09% (95% CI: 8.75-11.50%), Central 7.81% (95% CI: 5.34-10.71%), and Eastern African region 4.87% (95% CI: 3.77-6.11%) and lower prevalence were observed in Southern 2.47% (95% CI: 0.54-5.75%) followed by Northern Africa region with 1.73% (95% CI: 0.45-3.79%). Additionally, based on the date of publication, we found that the highest prevalence was observed in studies published between 2001 and 2010 (9.41, 95% CI: 7.19-11.90) and the lowest prevalence was observed in studies published between 2011 and 2024 (6.26%; 95% CI: 5.19-7.42).ConclusionThe seroprevalence of HBsAg among blood donors in Africa is still very high and heterogeneous. Therefore, intensifying the screening and vaccination of the population for Hepatitis B is critical to ensure blood safety toward eliminating Hepatitis B in Africa.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=395616, PROSPERO CRD42023395616.